You're The Voice – Try and Understand it: Some Practical Problems of the Citizens Initiated Referenda Act - Goschik, Ben (Victoria University of Wellington Law Review, 2003)
This paper examines the New Zealand’s Citizens Initiated Referenda Act 1993. The first part of the paper examines the democratic nature of the ‘direct democracy’ of citizens initiated referenda. The second part of the paper tackles certain of the practical concerns that flow from the legislation and the process that the legislation requires. In particular, the paper considers the uneasy relationship between the Clerk of the House and the role that the Clerk plays in determining the referendum question. Then, the paper examines problems concerning the referendum question itself, considering the limitation of only allowing a ‘yes’ or ‘no’ answer, as well as questions that ‘demand’ one answer over the other or raise more than one issue. The author argues that there is a real concern surrounding the ability of citizens initiated referenda to improve the democratic process through involving people in the legislative process.